2008
DOI: 10.2186/jjps.52.160
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Resilient Denture Liner in Mandibular Complete Denture on the Satisfaction Ratings of Patients at the First Appointment following Denture Delivery

Abstract: Despite the limitation of a short-term observation, the mandibular satisfaction ratings were dramatically higher in RLD wearers than in ARD wearers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 18 publications
1
24
0
Order By: Relevance
“…As many as 93% of patients participating in a six-year clinical study conducted by Schmidt et al [20,21] reported that dentures with soft linings were more comfortable than hard acrylic dentures. The use of LTSDLs is characterized by markedly improved speech and ability to chew, significantly reduced feelings of pain and oral soreness under the dentures, better retention and stability of the dentures, an increase in psychological comfort and longer denture wearing times [22,23,24]. The maximum occlusal force can significantly increase with LTSDLs [25,26]; however, other investigations have not confirmed this finding [27,28].…”
Section: Clinical Effects Of Long-term Soft Denture Liningsmentioning
confidence: 99%
See 1 more Smart Citation
“…As many as 93% of patients participating in a six-year clinical study conducted by Schmidt et al [20,21] reported that dentures with soft linings were more comfortable than hard acrylic dentures. The use of LTSDLs is characterized by markedly improved speech and ability to chew, significantly reduced feelings of pain and oral soreness under the dentures, better retention and stability of the dentures, an increase in psychological comfort and longer denture wearing times [22,23,24]. The maximum occlusal force can significantly increase with LTSDLs [25,26]; however, other investigations have not confirmed this finding [27,28].…”
Section: Clinical Effects Of Long-term Soft Denture Liningsmentioning
confidence: 99%
“…These patients will continue to use acrylic dentures that can cause pain and mucosal abrasions [22]. The use of LTSDLs will facilitate their adaptation to new dentures [23] and improve the process of rehabilitation, which should be reflected by fewer potential denture corrections and a resulting decrease in treatment costs. Thus, LTSDLs constitute a prospective group of dental materials, and previously reported clinical problems with LTSDLs [7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,31,32] justify further research aimed at improving their properties.…”
Section: Clinical Effects Of Long-term Soft Denture Liningsmentioning
confidence: 99%
“…These materials ensure an even distribution of the functional loads on the denture bearing area, restore the inflamed mucosa and improve patient's comfort [12][13][14][15][16][17][18][19] . Their cushioning effect has been reported to contribute substantially to denture wearers' satisfaction and their Oral Health Related Quality of Life (OHRQoL) [20][21] .…”
Section: Introductionmentioning
confidence: 99%
“… 10 suggested that the wearing of a denture significantly affected the quality of life of elderly persons. Despite the wide use and acceptance of soft liners, only a few studies evaluated the patient’s response about the use of these materials with regard to improvement in oral health related quality of life (OHRQoL) 10–12 . Kimoto et al.…”
Section: Introductionmentioning
confidence: 99%